Bridging Tradition and Innovation: A Systematic Review and Bibliometric Analysis of Turkish Fermented Foods - Kahraman Ilikkan, Ozge; Bagdat, Elif Seyma; Yilmaz, Remziye; Cetin, Bulent; Con, Ahmet Hilmi; Erten, Huseyin; Goksungur, Mehmet Yekta; Simsek, Omer (MDPI, 2025)
Background: Traditional fermented foods from T & uuml;rkiye are integral components of the nation's culinary heritage, reflecting a remarkable diversity shaped by local practices and ecosystems. These products embody region-specific microbial communities, often conceptualized as a microbial terroir, which influence their sensory qualities, nutritional value, and health-promoting properties. Methods: This study followed the PRISMA 2020 guidelines and included a systematic review and bibliometric analysis. A structured search was conducted in the Web of Science Core Collection (WoSCC) on 15 January 2025 using predefined keywords related to Turkish fermented foods and fermentation processes. Records were screened based on language (English or Turkish) and document type (articles, reviews, book chapters, and early access). A total of 1464 studies met the eligibility criteria, reflecting a 2.81% annual growth rate and a 12.7% international co-authorship rate. Bibliometric analysis was performed using the bibliometrix R package (RStudio 2024.12.1) and the biblioshiny interface. Results: The analysis revealed that the diversity of microbial consortia in Turkish fermented foods contributes to their distinctive characteristics, including enhanced nutritional profiles, probiotic potential, and food safety attributes. Emerging studies employing omics technologies-such as next-generation sequencing, metagenomics, and metabolomics-have expanded our understanding of fermentation ecosystems. Additionally, the growing integration of artificial intelligence supports predictive modeling and process optimization for advanced quality control. Conclusion: This synthesis highlights the significant technological, nutritional, and cultural value of T & uuml;rkiye's traditional fermented foods. Future directions should include omics-based translational research, indigenous starter culture development, and strengthened international collaborations to support sustainable and competitive functional food innovation.
Keywords: T & uuml; rkiye (Turkey); traditional fermented foods; fermentation; microbial terroir; functional foods; METAGENOMIC ANALYSIS; MICROBIAL COMMUNITY; SENSORY PROPERTIES; STARTER CULTURES; QUALITY; BEVERAGE; SHALGAM; SAUSAGE; TARHANA; JUICE; Food Science & Technology